ChemInform Abstract: The Direct α‐C(sp3)—H Functionalization of N‐Aryl Tetrahydroisoquinolines via an Iron‐Catalyzed Aerobic Nitro‐Mannich Reaction and Continuous Flow Processing. Issue 22 (15th May 2015) - Brzozowski, Martin; Forni, Jose A.; Savage, G. Paul; Polyzos, Anastasios
Abstract: The efficient aerobic nitro‐Mannich reaction of N‐aryl tetrahydroisoquinolines using simple Fe salts and molecular O2 is reported.